P19 Worrying Trend Of Labelling Ambiguous Deaths As Pneumonia And Potential Impact On Respiratory Service In A District General Hospital. (14th November 2013) - Tan, EL; Davies, E; Javed, S; Sundar, R; Aziz, I
Abstract : Background: Pneumonia is a common cause of death recorded on death certificates. This data is used by Dr Foster to calculate hospital specific mortality rate (HSMR). However there is a general impression that pneumonia is recorded as the cause of death without confirmation. The British Thoracic Society (BTS) defines pneumonia as 'symptoms and signs consistent with an acute lower respiratory tract infection associated with new radiographic shadowing for which there is no other explanation' Aims: Our aim was to establish if patients reported to have died of pneumonia had radiographic shadowing in accordance with the BTS definition and if they have been managed with appropriate antibiotics as per BTS guidelines 1 . Methods: We reviewed the case notes and chest x-rays (CXR) of 111 consecutive patients where pneumonia was stated as the cause of the death. We also investigated whether correct antibiotic therapy was used as per hospital guidelines. Results: 111 patients (53 male, mean age 80.6) were given diagnosis of pneumonia on their death certificates as follows; aspiration pneumonia 20 patients, bronchopneumonia 8 patients, community acquired pneumonia 19 patients, pneumonia 44 patients and hospital acquired pneumonia 20 patients. Out of these 111 patients, 75 (67.6%) patients had radiological changes consistent with a diagnosis of pneumonia on CXR. Out of these 75 patients with radiologically confirmed pneumonia 29 (38.7%) were given incorrect antibiotics as they were treated mainly for sepsis. Conclusions: Our findings show a very worrying trend of incorrectly recording pneumonia as cause of death in a third of patients, who were given pneumonia as cause of death. This would increase the HSMR for pneumonia as calculated by Dr Foster. In our opinion pneumonia as a cause of death is an easy option for many medical practitioners. Recommendations: We recommend an early input by respiratory physicians for all respiratory admisssions to make sure that respiratory illnesses are managed correctly. References: Thorax 2009; 64 (Supplement III) : 1–61.